Study of the genetic and molecular epidemiology of cystic fibrosis based on the patient registry for planning targeted therapy in Russian Federation - Kondratyeva, Elena; Melyanovskaya, Yuliya; Sherman, Victoriya; Voronkova, Anna; Zhekaite, Elena; Krasovsky, Stanislav; Amelina, Elena; Kashirskaya, Nataliya; Shadrina, Vera; Polyakov, Alexander; Adyan, Tagui; Sсhagina, Olga; et al. (Frontiers in Genetics, 2024)
Cystic fibrosis (CF) is a genetically inherited disorder characterized by a wide range of clinical manifestations and genetic variations. This study focuses on the genetic and molecular epidemiology of CF in the Russian population, utilizing data from the national CF registry. The birth prevalence of CF in Russia has been analyzed over a span of years, revealing variations in frequency. The study delves into the genetic landscape of CFTR gene variants in Russian patients, showcasing a diverse spectrum with a predominance of severe variants, some of which are rare and distinct from global populations. A total of 233 variants have been documented, exhibiting frequencies ranging from 0.01% to 51.5%, with 47 of these variants remaining uncharted within international genetic databases. As of 2021, CFTR modulator therapy has been introduced for patients under 19 years, heightening the importance of genetic diagnosis. In 2023, more than 1,850 patients under 19 received CFTR modulator therapy. Notably, the impact of complex alleles on disease progression and response to targeted therapies is gaining recognition. Comparisons with European registries highlight distinctive features of the Russian population, such as differences in age distribution among patients. Additionally, the study emphasizes the need to ascertain clinical significance and pathogenicity of newly identified genetic variants, along with exploring their suitability for targeted therapies. The integration of genetic in-sights into the management of CF offers potential for enhanced personalized therapeutic interventions. In conclusion, this thorough analysis provides a comprehensive understanding of the genetic nuances within the Russian CF population. By il-luminating the intricate relationship between genetic variations and disease manifestation, the study underscores the essential role of genetics in shaping therapeutic strategies and improving patient outcomes. Further research and ongoing genetic ex-ploration are crucial for optimizing the care of individuals with CF in the era of evolving therapeutic options.